Design and manufacture of a novel system to simulate the biomechanics of basic and pitching shoulder motion. Issue 5 (May 2012) - Entezari, V.; Della Croce, U.; DeAngelis, J. P.; Ramappa, A. J.; Nazarian, A.; Trechsel, B. L.; Dow, W. A.; Stanton, S. K.; Rosso, C.; Müller, A.; McKenzie, B.; Vartanians, V.; et al.
Abstract : Objectives: Cadaveric models of the shoulder evaluate discrete motion segments using the glenohumeral joint in isolation over a defined trajectory. The aim of this study was to design, manufacture and validate a robotic system to accurately create three-dimensional movement of the upper body and capture it using high-speed motion cameras. Methods: In particular, we intended to use the robotic system to simulate the normal throwing motion in an intact cadaver. The robotic system consists of a lower frame (to move the torso) and an upper frame (to move an arm) using seven actuators. The actuators accurately reproduced planned trajectories. The marker setup used for motion capture was able to determine the six degrees of freedom of all involved joints during the planned motion of the end effector. Results: The testing system demonstrated high precision and accuracy based on the expected versus observed displacements of individual axes. The maximum coefficient of variation for displacement of unloaded axes was less than 0.5% for all axes. The expected and observed actual displacements had a high level of correlation with coefficients of determination of 1.0 for all axes. Conclusions: Given that this system can accurately simulate and track simple and complex motion, there is a new opportunity to study kinematics of the shoulder under normal and pathological conditions in a cadaveric shoulder model.